Effectiveness of the Guarantee Letter in the Bank's Obligation towards the Beneficiaries - Dawood Salman, Lect. Murtaja (Basra studies journal, 2025)
Despite the advantages that the guarantee letter offers and its effectiveness in commercial transactions, this effectiveness can be affected in several cases. For instance, the bank may be obligated to refrain from paying the amount of the guarantee letter if the request for the encashment of the letter involves fraud, or in the event of a temporary order suspending the disbursement of the guarantee amount. Furthermore, its effectiveness diminishes in situations where the beneficiary's creditors seek to impose a lien.